Development of acetazolamide-loaded, pH-triggered polymeric nanoparticulate in situ gel for sustained ocular delivery: in vitro. ex vivo evaluation and pharmacodynamic study. (September 2014) - Singh, Jyotsana; Chhabra, Gulshan; Pathak, Kamla
Abstract The objective of research was to develop a novel pH-triggered polymeric nanoparticulate in situ gel (NP-ISG) for ophthalmic delivery of acetazolamide (ACZ) to enhance the conjunctival permeation and precorneal residence time of the formulation by overcoming the limitations of protective ocular barriers. Nanoparticles (NP1–NP12) were developed by nanoprecipitation method and evaluated for pharmacotechnical characteristics including transmission electron microscopy. The optimized formulation, NP10 was dispersed in carbopol 934 P to form nanoparticulate in situ gels (NP-ISG1–NP-ISG5). NP-ISG5 was selected as optimized formulation on the basis of gelation ability and residence time. Ex vivo transcorneal permeation study exhibited significantly higher ACZ permeation from NP-ISG5 (74.50 ± 2.20 mg/cm2) and NP10 (93.5 ± 2.25 mg/cm2) than eye drops (20.08 ± 3.12 mg/cm2) and ACZ suspension (16.03 ± 2.14). Modified Draize test with zero score indicated nonirritant property of NP-ISG5. Corneal toxicity study revealed no visual signs of tissue damage. Further, NP-ISG5 when tested for hypotensive effect on intraocular pressure (IOP) in rabbits revealed that NP-ISG5 caused significant decrease in IOP (p < 0.05) in comparison to eye drops. Conclusively, NP-ISG5 may offer intensive management of glaucoma via higher permeation, prolonged precorneal residence time and sustained drug release along with higher in vitro efficacy, safety and patient compliance.